THE EFFECT OF MINDFULNESS THROUGH SMARTPHONE APPLICATIONS ON THE ANXIETY OF FINAL-LEVEL NURSING STUDENTS - Reza Indra Wiguna; Meidiana Dwidiyanti; Sri Padma Sari (International Journal of Nursing and Health Services (IJNHS), 2019)
Abstract Anxiety in nursing students have been shown to have an impact on the body. This study aims to determine the effect of mindfulness training by using smartphone applications on anxiety in the group of final level nursing students in Indonesia. This study uses a quasi-experimental design with pre-test and post-test design. The number of samples was 77 students, divided into 38 respondents in the intervention group and 39 respondents in the control group. The intervention group was given mindfulness training by using the smartphone application in four meetings for two weeks, whereas the control group was given mindfulness training after the study in the fifth week. Anxiety is measured by the Zung Self Rating Anxiety Scale (ZSRAS) instrument. Data analyze by using Mann-Whitney and Wilcoxon tests. The results of this study indicate that the average value of anxiety in the intervention group before the study was 43.55 (± 3.92), and there was a decrease after mindfulness training to 36.50 (± 4.77) (p = .000). Whereas in the control group the average anxiety value was 44.23 (± 4.36), and there was an increase in anxiety to 45.00 (± 5.04) in the post-test with a value (p = .813). Mindfulness training through smartphone devices SIMBA application has a significant effect on reducing anxiety levels in final-year nursing students. This intervention could be done independently to overcome psychological problems that often interfere with the learning process of nursing students in the academic environment. Keywords: Anxiety, Nursing students, Mindfulness, Smartphone